Effect of Cigarettes Smoking on Embryo Development through its Effect on Sperm DNA Fragmentation - A Systematic Review - Margiana, Dr. Ria (Asian Journal of Pharmaceutics (AJP), 2018)
Background: The negative deleterious effects of cigarette smoking are widely known, especially the relationship its influence on semen quality and sperm DNA fragmentation. Male cigarette smoking was highlighted and hypothesized to not only affect cause DNA fragmentation but also affect the early embryo development. To summarize various literature studies, a systematic review of relevant observational studies was conducted to determine the relationship between cigarette smoking among men and DNA fragmentation and the ultimate influence on embryo development. Methods: A methodical explore of the observational literature on the subject was carried out on Google Scholar. All papers relevant observational papers reporting on the tie of cigarette smoking with sperm DNA fragmentation and embryo growth were included. The retrieval of pertinent reports was done and subsequently the systematic search of reference lists to help in the identification of studies qualifying for inclusion. Results: Of the 14 studies, 4 papers were retrieved reporting observational findings that cigarette smoking causes adverse DNA damage which is evidentially correlated with poor embryo growth. However, the remaining studies had no information implying any existent relationship between cigarette smoking, DNA damage, and development of the embryo. Conclusions: The literature asserts that cigarette smoking through sperm DNA fragmentation affects early embryonic development. Well-designed research literature with evidence-based, pre-defined criteria for subject selection, the definition of cigarette smoking, and its contents are essential in achieving consistent affirmation on the result of smoking on DNA fragmentation and ultimately, embryo development.